Analysis of Audience Reception Against Intercultural Communication Represented in the Film Bumi Manusia - Fadilah Amelia; Firda Yulia; Natasya Asali; Hassan Sazali; Maulana Andinata Dalimunthe (Penerbit Jurnal Indonesia, 2022)
Bumi Manusia is a film by Pramoedya Ananta Toer which has a theme about the love story of a young man of Javanese descent with a girl of Dutch descent and his struggles in the midst of the early 20th century Indonesian movement. audience, how to interpret the message received from a media, namely from a film which is one of the mass communication media. The purpose of this study is to find out how the audience's reception of intercultural communication in the film Bumi Manusia. This research is a descriptive analytical research method using Stuart Hall reception analysis with the concept of encoding-decoding and data collection techniques using the interview method. This study succeeded in showing different audience receptions in interpreting intercultural communication in the film Bumi Manusia. The results of this study indicate, the audience perceives into three types of dominant hegemonic, negotiated reading and optional reading. Viewers who are included in this dominant hegemonic classification understand the message content as it is. Audiences who are in a negotiating position receive texts or scenes of intercultural communication in the film but are not fully accepted because there are still things to negotiate. While the audience is in an oppotional position, the audience does not accept the text or scenes of intercultural communication presented in the film.